2004
DOI: 10.1161/01.hyp.0000115384.01463.61
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Dynamic Responses of Renal Sympathetic Nerve Activity to Air-Jet Stress in Sinoaortic Denervated Rats

Abstract: Abstract-This study examined the role of arterial baroreceptors in mediating the relationship between changes in the mean level and the amplitude of slow oscillations of renal sympathetic nerve activity (RSNA) during environmental stress. In 7 sham-operated (control) and 7 chronically (2 weeks before study) sinoaortic baroreceptor denervated (SAD) conscious rats, arterial pressure (AP) and RSNA were simultaneously recorded during two 15-minute periods, before and during the application of a mild environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 36 publications
(41 reference statements)
4
28
1
2
Order By: Relevance
“…The reason is twofold. First, effects of air-jet stress on fast rhythms of AP have been thoroughly described in rats (2,4,12). Secondly, an increased sympathetic baroreflex gain is expected to attenuate low and very low frequency components of AP variability (5,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is twofold. First, effects of air-jet stress on fast rhythms of AP have been thoroughly described in rats (2,4,12). Secondly, an increased sympathetic baroreflex gain is expected to attenuate low and very low frequency components of AP variability (5,15).…”
Section: Discussionmentioning
confidence: 99%
“…IN LABORATORY ANIMALS AND human subjects, emotional stress evokes parallel increases in arterial pressure (AP), heart rate (HR), and sympathetic nerve activity (SNA) (1,2,17). In sleeping or quiet resting subjects, pharmacologically induced increases in AP result in reflex decreases in HR and SNA.…”
mentioning
confidence: 99%
“…First, because pilot experiments showed that patients were often not able to perform frequency-controlled quiet breathing in an adequate manner before anesthesia induction and were irritated with placing invasive radial arterial line, we decided to design this study as an externally controlled study and to perform the recordings with an awake control group, who served as negative control to compare with an anesthesia baseline state before surgical incision. Second, we used coherence [0.5 as a threshold to detect a significant level of linear coupling based on a De Boer's work [28], however, different threshold values might be a more adequate approach, based on the assessment of degree of freedom of the cross-spectral approach [29]. Third, we only assessed the spontaneous BRS but not the pharmacological BRS, therefore further study will be required to probe systemically the uncoupling of BP-HR modulation by the baroreflex.…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se, ainda, que o estresse pode levar a alterações no sistema circulatório, dependendo do tipo de estressor envolvido (Esch et al, 2002), uma vez que a exposição ao estresse provoca o aumento da PA e da FC (Irvine et al, 1997, Barres et al, 2004, Carrive, 2006, Tavares and Correa, 2006. Adicionalmente, alterações cardiovasculares provocadas por pelo estresse crônico são seguidas por alterações da atividade do barorreflexo (Duarte et al, 2015a) O barorreflexo é um dos mecanismos neurais responsáveis pelo ajuste em curto prazo da PA através da modulação de atividades simpática e parassimpática para o sistema cardiovascular, influenciando FC e resistência vascular (Huang et al, 2010).…”
Section: Sumáriounclassified
“…Além dessas alterações no peso e comportamento, vários estudos demonstram que o estresse pode levar a alterações no sistema circulatório, dependendo do tipo de estressor envolvido (Esch et al, 2002), uma vez que a exposição ao estresse provoca o aumento da PA e da FC (Irvine et al, 1997, Barres et al, 2004, Carrive, 2006, Tavares and Correa, 2006, Grippo et al, 2008, Duarte et al, 2015b. Nossos achados estão em conformidade com estudos de Grippo et al, (2006) Embora as alterações cardiovasculares sejam comuns frente à exposição ao estresse, elas podem variar de acordo com os diferentes estressores utilizados (Crestani et al, 2010c).…”
Section: Figura 38 (Ab)unclassified